Obesity and vitamin D deficiency: a systematic review and meta‐analysis - Pereira‐Santos, M; Costa, P. R. F; Assis, A. M. O; Santos, C. A. S. T; Santos, D. B (Obesity reviews, 2015)
Over the past decade, there have been an increasing number of studies on the association between vitamin D deficiency and anthropometric state. However, we did not identify any meta‐analyses of the relationship between obesity and vitamin D deficiency in different age groups. Thus, we evaluated the association between obesity and vitamin D deficiency. We searched for observational studies published up to April 2014 in PubMed/Medline, Web of Science and Scopus databases. We performed a meta‐analysis in accordance with the random‐effects model to obtain the summary measurement (prevalence ratio, PR). Among the 29,882 articles identified, 23 met the inclusion criteria. The prevalence of vitamin D deficiency was 35% higher in obese subjects compared to the eutrophic group (PR: 1.35; 95% CI: 1.21–1.50) and 24% higher than in the overweight group (PR: 1.24; 95% CI: 1.14–1.34). These results indicate that the prevalence of vitamin D deficiency was more elevated in obese subjects. The vitamin D deficiency was associated with obesity irrespective of age, latitude, cut‐offs to define vitamin D deficiency and the Human Development Index of the study location.